Mejoramiento genético y actividades relacionadas. Mejoramiento de características individuales. Habichuela - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Snap bean improvement at CIAT has been carried out collaboratively with Washington State U. since 1983, to incorporate disease resistance and tropical adaptation from the dry bean improvement programs into green beans. An international adaptation nursery of advanced snap bean lines was distributed to 14 countries in Asia, Africa, Europe, and America. The current nursery consists of 204 bush and 32 climbing lines. In collaboration with the Instituto Colombiano Agropecuario, a regional trial of 19 and 14 bush and climbing snap bean lines, resp., was distributed. All climbing lines were resistant to anthracnose, the best being HAB 208, HAB 214, HAB 232, HAB 234, HAB 235, and HAB 236. Bush lines HAB 87, HAB 141, and HAB 173 were resistant to anthracnose, rust, and BCMV. (CIAT)